African Spiritual Traditions in the Novels of Toni Morrison - Zauditu-Selassie, K. (Book collections on Project MUSE., 2009)
Toni Morrison herself has long urged for organic critical readings of her works. K. Zauditu-Selassie delves deeply into African spiritual traditions, clearly explaining the meanings of African cosmology and epistemology as manifest in Morrison's novels. The result is a comprehensive, tour-de-force critical investigation of such works as The Bluest Eye, Sula, Song of Solomon, Tar Baby, Paradise, Love, Beloved , and Jazz .